The (4;11)(q21;q23) chromosome translocations in acute leukemias involve the VDJ recombinase. - Gu, Y (1992)
Chromosomal region 11q23 is frequently rearranged in acute lymphocytic leukemias (ALLs) and in acute myeloid leukemias (AMLs), mostly in reciprocal exchanges with various translocation partners. The most common of these translocations is t(4;11)(q21;q23). It is present in approximately 10% of ALL patients, most frequently in very young children. We have recently cloned a region of chromosome 11, the ALL-1 locus, found to be rearranged in malignant cells from patients with the t(4;11), t(9;11), t(11;19), t(1;11), t(6;11), t(10;11), and del(11q23) chromosomal abnormalities. Here we report the cloning and characterization of chromosomal breakpoints from leukemic cells with t(4;11) aberrations. The breakpoints cluster in regions of 7-8 kilobases on both chromosomes 4 and 11. The presence of heptamer- and nonamer-like sequences at the sites of breakage suggests that the VDJ recombinase utilized for immunoglobulin gene rearrangement is also directly involved in these translocations. We also show that leukemic cells with t(4;11) express altered RNAs transcribed from the derivative chromosomes 11 and 4.